2005
DOI: 10.1007/s10681-005-7072-0
|View full text |Cite
|
Sign up to set email alerts
|

Maize commercial hybrids compared to improved population hybrids for grain yield and agronomic performance

Abstract: Improved maize (Zea mays L.) populations and population hybrids can both be profitable alternatives to commercial single-cross hybrids as well as good elite sources of diverse inbred lines. The objective of this research was to compare grain yield and agronomic performance between early maturing maize population hybrids and current early maturing commercial single-cross hybrids. This is a consequence of our research program targeted at identifying alternative heterotic patterns for the northern Corn Belt. Impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 11 publications
3
45
1
5
Order By: Relevance
“…Sprague noted "it appears that the ear-to-row method of selection for yielding ability was discredited not because of genetic limitations of the method, but because of the inadequate field plot technique" [16]. Research after Richey's 1922 conclusion showed recurrent selection and varietal hybrids could be very successful at increasing maize yields after all, although they could not provide cultivars with the yields of the best hybrids [35,47,81,95,119,120,[126][127][128][129][130][131].…”
Section: Recurrent Selection Revisitedmentioning
confidence: 99%
“…Sprague noted "it appears that the ear-to-row method of selection for yielding ability was discredited not because of genetic limitations of the method, but because of the inadequate field plot technique" [16]. Research after Richey's 1922 conclusion showed recurrent selection and varietal hybrids could be very successful at increasing maize yields after all, although they could not provide cultivars with the yields of the best hybrids [35,47,81,95,119,120,[126][127][128][129][130][131].…”
Section: Recurrent Selection Revisitedmentioning
confidence: 99%
“…In the meantime, the NDSU program is helping produce a sustainable crop under intense drought for a better utilization by ethanol plants without additional transportation and fossil fuel costs. The NDSU maize population-hybrid concept has been recognized as a profitable alternative method of maize hybrid production (Carena 2005a, Carena andWicks III 2006) and it is currently being tested commercially in central and western ND for ethanol utilization.…”
Section: Moving Maize West: Short-season Drought Tolerancementioning
confidence: 99%
“…Therefore, improved maize populations allow the development of new lines with a good capacity of recombining amongst each other. In addition, there is the possibility of boasting more and more compensatory increments according to the breeding among divergent lines (Carena, 2005).…”
Section: Introductionmentioning
confidence: 99%